I will let D be a function that contains elements n from the set of Natural Numbers: N

i define D(n) = 2 x 3^c

.... .. .................. c=0

(b) Prove this sentance by induction:

for all n which are elements from set Natural Numbers: N, D(n) = 3^(n+1) +1

Base case: when n is 1 D(1) = 3^(1+1) + 1 = 9 + 1 = 10

Inductive step: we assume that D(n) = 3^(n+1) is true for n = k, hence D(k) = 3^(k+1) + 1 is true

We prove that D(k) = 3^(k+1) + 1

sorry for my english i am from italy. this is what im quite unsure about what is happen here and if im doing it right, how do i prove now?